Health financing for the poor in the Philippines: Final report - Michael R. Cabalfin (Philippine Institute for Development Studies (PIDS), 2016)
Indigent membership in PhilHealth has surged in recent years, driven by the nation-wide identification of the poor. However, the massive identification has led to the enrollment of more members than official poverty estimates, resulting in leakages in the government's social health insurance subsidy. The massive enrollment has been facilitated by the incremental revenues from the revised sin tax law. Subsidy for the poor now comprises over a third of the national health insurance fund, effectively subsidizing health-care services for other members, especially the informal sector. Hospitals also enroll the poor as well as the near poor in PhilHealth at point of care and may oversubscribe the poor given the higher reimbursement relative to the premium subsidy. The poor are covered by a No Balance Billing policy in which they are not liable to pay hospital fees over the case rate. Despite this, close to half of the poor still incur out-of-pocket expenses, especially for medication. Close to three-fourths of the poor are also covered by the Primary Care Benefit 2 Package, which pays for outpatient medicines for certain illnesses to prevent catastrophic conditions. Finally, close to 1 percent of the benefits for the poor is estimated to fall under the Z benefit package, which subsidizes catastrophic illnesses.
Keywords: 330; health insurance; poverty; social protection